Limits of grazing area use by feral Greylag Geese Anser anser during moult - Schwartz, Konrad; Woog, Friederike (Wildfowl, 2012)
Use of grazing areas by feral Greylag Geese Anser anser was studied from May– September 2010 to compare grazing pressure at two feeding sites during and after moult. Grazing pressure was determined from weekly counts of goose droppings within random 5 m2 plots; vegetation height and composition were measured to determine whether variation in food supply influenced the extent to which geese used the two sites. Distance from the water’s edge explained much of the variation in goose grazing across sites, with birds less likely to use areas furthest from open water during moult.